Transaction Cost on The Implementation of E-Invoices in Micro and Small Enterprises - Clara Palupi; Darwanto Darwanto (Signifikan: Jurnal Ilmu Ekonomi, 2017)
E-invoice is one of the tax administration modernization program created to reduce the tax compliance costs in order to improve the tax compliance. This paper aims to prove that e-invoice as a form of institutional change can actually change or lower the tax compliance costs. Using a qualitative approach case study method and supported by evidence of calculation of the cost of compliance. The results showed that e-invoice cannot directly reduce the tax compliance costs, because e-invoice is a new program and the taxpayers bear big the amount of time cost for the process of adjustment (adapt). Tax compliance costs will increase temporarily during the adaptation process; the total compliance cost in the six months after the e-invoice increased 3.4 percent from the six months before. Then, the results of tax compliance costs estimated at one year after the e-invoice applied showed that the compliance costs decrease 31 percent from the cost of compliance without e-invoice.DOI: 10.15408/sjie.v6i1.4866